Labour legislation and performance among small enterprises in the Gauteng province of South Africa - Okharedia, Akhabue Anthony (My University, 2016)
The principal aim of this study is to analyse how the three (3) labour legislations, namely, (a) the Labour Relations Act 66 of 1995, (b) the Basic Conditions of Employment Act 75 of 1997 and (c) the Employment Equity Act 55 of 1998 influence the growth, management and governance of small enterprises in Gauteng Province of South Africa. This research also investigates if the complete exclusion, selective exclusion or parallel application of the above three labour legislations will help in the management, growth and good governance of small enterprises in Gauteng Province. In addition to the above issues, this research also investigates how disputes are resolved in small enterprises. Furthermore, this research investigates the issue of organisational rights in small enterprises.To investigate all the above issues, the researcher used both qualitative and quantitative research techniques and both techniques were quite useful in the data analysis.The inference that was drawn from the data analysis is that application of the three (3) labour legislations in terms of complete exclusion, selective exclusion and parallel application of the three labour legislations is very important for the growth, management and good governance of small enterprises and this is fully discussed in the thesis. The analysis of the research data indicates that small enterprises cannot benefit from the organisational rights entrenched in the Labour Relation Act of 1995 and the reasons for this are discussed in the thesis. This research also found that small enterprises cannot resolve their disputes efficiently through the current process of dispute resolution as stipulated in Section 135 of the LRA. The reasons why small enterprises find it difficult to follow the process is discussed in the thesis. The recommendations in this thesis, attempt to offer solutions to the identified problems.
Submitted in accordance with the requirement for the degree of Doctor of Philosophy in Business Administration at the University of the Witwatersrand Johannesburg March 2016
Keywords: Industrial relations--South Africa; Labor laws and legislation--South Africa; Small business--South Africa